Translation to Serbian and transcultural adaptation of the oral health-related quality of life [OHQoL-UK(W)] instrument - Milošević, Marija; Živanović, Suzana; Janković, Slobodan M (Vojnosanitetski pregled, 2021)
Background/Aim. Measuring health-related quality of life is of great help to clinicians when they have to choose optimal therapy for their patients or estimate its effects. The aim of this study was to translate the oral health-related quality of life [OHQoL-UK(W)] questionnaire from English to Serbian, to make necessary cultural adaptations of the translation, and to test its reliability in a sample of adult Serbian patients. Methods. After obtaining permission from the authors, translation and cultural adaptation of the OHQoL-UK(W) was made according to the International Society for Pharmacoeconomics and Outcomes Research (ISPOR) guidelines. Reliability of the Serbian translation was tested on a sample of 250 patients through calculation of Cronbach’s alpha, as a measure of internal consistency. Results. Serbian translation of the OHQoL-UK(W) had very similar degree of internal consistency (Cronbach’s alpha 0.947), and correlated satisfactorily with the visual analogue scale (VAS) score and inversely with the Decay-missing-filled teeth (DMFT) index. Factorial analysis revealed only one factor, as in the original scale. Conclusions. Serbian translation of the OHQoL-UK(W) is reliable instrument for measuring oral health-related quality of life in adult dentistry patients.
Keywords: oral health; surveys and questionnaires; serbia; quality of life